2020
DOI: 10.1021/acs.jpclett.0c00713
|View full text |Cite
|
Sign up to set email alerts
|

Spin Thermometry: A Straightforward Measure of Millikelvin Deuterium Spin Temperatures Achieved by Dynamic Nuclear Polarization

Abstract: Dynamic nuclear polarization of samples at low temperatures, typically between 1.2 and 4.2 K, allows one to achieve spin temperatures as low as 2 mK, so that for many nuclear isotopes the high-temperature approximation is violated for the nuclear Zeeman interaction. This leads to characteristic asymmetries in powder spectra. We show that the lineshapes due to the quadrupolar couplings of deuterium spins present in virtually all solvents used for such experiments ('DNP juice') allows the quick yet accurate dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…This is opposite to the case of strongly polarized water (Mammoli et al, 2015), and other systems (Aghelnejad et al, 2020), where the peak intensities become more unequal with increasing 1 H polarization PH. A similar curve for the case of negative microwave irradiation is shown in the Supplement.…”
Section: C Nmr Peak Asymmetry Vs 1 H Polarizationcontrasting
confidence: 68%
“…This is opposite to the case of strongly polarized water (Mammoli et al, 2015), and other systems (Aghelnejad et al, 2020), where the peak intensities become more unequal with increasing 1 H polarization PH. A similar curve for the case of negative microwave irradiation is shown in the Supplement.…”
Section: C Nmr Peak Asymmetry Vs 1 H Polarizationcontrasting
confidence: 68%
“…It has been shown that such echoes do not affect the microwave-driven build-up of the hyperpolarization. 13 A saturating train of 100 proton pulses with τp = 4 μs ( = 36°) spaced by 100 μs was applied prior to all experiments. To a good approximation, the effect of a pair of 9° pulses on the polarization can be neglected: two closely spaced pulses with  = 9° merely attenuate the polarization by a factor cos 2  = 0.975.…”
mentioning
confidence: 99%
“…Although complete refocusing of both linear and quadratic interactions cannot be achieved by such echoes, they nonetheless remove deleterious background signals and acoustic ringing of the probe. It has been shown that such echoes do not affect the microwave-driven buildup of the hyperpolarization . A saturating train of 100 proton pulses with τ p = 4 μs (β = 36°) spaced by 100 μs was applied prior to all experiments.…”
mentioning
confidence: 99%
“…Greater deviations over a smaller range of spin temperatures have been shown in the context of 2 H DNP thermometry. 37 Lineshape polarimetry has also proven to be an advantageous tool to measure the 15 N polarization of hyperpolarized 15 N 2 O in the solid-state. 49 Indirect measurements of 1 H polarizations by using 13 C lineshape polarimetry of 13 CH 3 groups has also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of small flip angle rf -pulses in low temperature experiments has previously unveiled asymmetries in NMR spectra. 27,34–37 During the DNP build-up time, small flip angle rf -pulses are necessary to monitor the 1 H hyperpolarization without measurably diminishing it. 38,39 The proton NMR signal is continuously monitored until a plateau in the signal intensity is reached.…”
Section: Methodsmentioning
confidence: 99%